Penguatan Positif untuk meningkatkan rawat diri pada anak Autism Spectrum Disorder - Resty Puspitaliani Irawan (Procedia : Studi Kasus dan Intervensi Psikologi, 2022)
Individuals with autistic disorders need to always be trained in terms of self-care by themselves. The purpose of this study was to increase self-care autonomy in children with autism, namely bathing, dressing and brushing their teeth. This research uses a qualitative case study approach with one subject. Collecting data using interview, observation and The Childhood Autism Spectrum Test (CAST). The intervention was carried out using the positive reinforcement method with reinforcements in the form of hugs and praise. The intervention was carried out in five sessions. The results of the intervention showed an increase in self-care skills in the form of bathing, dressing and brushing teeth. Thus it can be said that the positive reinforcement method can improve self-care autonomy in children with autism spectrum disorder.